The impact of teaching culture online during COVID-19. (September 2021) - Bennett, Bindi
This article speaks to an Aboriginal academic's experience during COVID-19 teaching cultural content via the Internet and an online platform. It highlights the challenges of teaching deeply spiritual content online in a unit where being able to develop relationships and trust before these units are offered would be beneficial.